THE RELATIONSHIP OF READING ANXIETY TOWARD READING STRATEGY ON GRADE EIGHT STUDENTS AT SMP NEGERI 3 BAUBAU - Irawan, Irawan (English Education Department, 2024)
Problem statement of this research was whether there was a significant and positive relationship of reading anxiety toward reading strategy on grade eight at SMP Negeri 3 Baubau. Objective of the research was to find out whether there was a significant and positive relationship ooff reading anxiety toward reading stratey on grade eight at SMP Negeri 3 Baubau. Data collection in this research was carried out using a research instrument in the form questionaire to determine the types of reading anxiety and readng strategy. The data obtained were analyzed by descriptive statistical analysis and inferential statistical analysis. The result of this research showed that there was not any significant and positive relationship between students’ reading anxiety and students’ reading strategy. This conclusion based on statistical analysis. Where the calculated F value of 0.004 with a significant value of 0.949. Because the calculated F value was greater and the F table and significant value was greater than ɑ (0.05). This meant that the null hypothesis was accepted and the alternative hypothesis was rejected.